2012
DOI: 10.1186/1297-9686-44-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on genomic predictions using three GBLUP methods and two single-step blending methods in the Nordic Holstein population

Abstract: BackgroundA single-step blending approach allows genomic prediction using information of genotyped and non-genotyped animals simultaneously. However, the combined relationship matrix in a single-step method may need to be adjusted because marker-based and pedigree-based relationship matrices may not be on the same scale. The same may apply when a GBLUP model includes both genomic breeding values and residual polygenic effects. The objective of this study was to compare single-step blending methods and GBLUP me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
126
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 26 publications
18
126
6
Order By: Relevance
“…no DNA sample available). It has been reported that including these bulls can increase prediction reliability by 1.3% point in Nordic Red ) and 1.6% point in Nordic Holstein (Gao et al, 2012).…”
Section: Genomic Prediction In Small Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…no DNA sample available). It has been reported that including these bulls can increase prediction reliability by 1.3% point in Nordic Red ) and 1.6% point in Nordic Holstein (Gao et al, 2012).…”
Section: Genomic Prediction In Small Populationsmentioning
confidence: 99%
“…This may be a more efficient use of LD between QTL and markers and results in a more constant LD between QTL and prediction markers over generations. Accordingly the superiority of Bayesian models over GBLUP, is larger when the relationship between test and reference animals is weak (Gao et al, 2012;Habier et al, 2013). This indicates that Bayesian variable selection models have the potential to utilize information across distantly related breeds and improve multi-breed evaluations.…”
Section: Models and Strategies To Focus In On Causative Variantsmentioning
confidence: 99%
“…In this study, ω = 0.20 was chosen according to the previous studies in Improving genomic predictions in Danish Jersey Nordic cattle populations 2012c;Gao et al, 2012). In this setting, the GBLUP model is equivalent to a GBLUP including a genomic effect and a residual polygenic effect accounting for 80% and 20% of total additive genetic variance, respectively.…”
Section: Datamentioning
confidence: 99%
“…Until now, only about 1200 to 1400 Danish progeny-tested bulls (depending on trait) are available to be used as reference bulls. Due to the small reference population, accuracy of genomic prediction in the Danish Jersey is much lower than in the Danish Holstein and Red Cattle populations 2012c;Gao et al, 2012;Thomasen et al, 2012). Therefore, it is important to find efficient approaches to improve accuracy of genomic prediction in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Přibyl et al (2012) used this methodology for the genetic evaluation of the relatively small Czech Holstein population. Gao et al (2012) and used DRP of sires instead of phenotypic production records as input data in ssGBLUP, naming the procedure the one-step blending approach. Its goal was to maximize prediction accuracy by optimally utilizing all possible information sources.…”
Section: Introductionmentioning
confidence: 99%